A Novel Multiple Risk Score Model for Prediction of Long-Term Ischemic Risk in Patients With Coronary Artery Disease Undergoing Percutaneous Coronary Intervention: Insights From the I-LOVE-IT 2 Trial - Qiu, Miaohan; Li, Yi; Na, Kun; Qi, Zizhao; Ma, Sicong; Zhou, He; Xu, Xiaoming; Li, Jing; Xu, Kai; Wang, Xiaozeng; Han, Yaling (Frontiers in Cardiovascular Medicine, 2022)
ABSTRACT Backgrounds: A plug-and-play standardized algorithm to identify the ischemic risk in coronary artery disease (CAD) patients undergoing percutaneous coronary intervention (PCI) could play a valuable step to help a wide spectrum of clinic workers. This study intended to investigate the ability of using the accumulation of multiple clinical routine risk scores to predict long-term ischemic events in CAD patients undergoing PCI. Methods: This was a secondary analysis of the I-LOVE-IT 2 (Evaluate Safety and Effectiveness of the Tivoli drug-eluting stent (DES) and the Firebird DES for Treatment of Coronary Revascularization) trial, which was a prospective, multicenter, randomized study. The Global Registry for Acute Coronary Events (GRACE), baseline Synergy Between Percutaneous Coronary Intervention with Taxus and Cardiac Surgery (SYNTAX), residual SYNTAX, and age, creatinine and ejection fraction (ACEF) score were calculated in all patients. Risk stratification was based on the number of these four scores met the established thresholds for the ischemic risk. The primary end point was ischemic events at 48 months, defined as the composite of cardiac death, nonfatal myocardial infarction, stroke, or definite/probable stent thrombosis (ST). Results: The 48-month ischemic events had a significant trend for higher event rates (from 6.61% to 16.93%) with incremental number of risk scores presenting the higher ischemic risk from 0 to ≥3 (P trend<0.001). The categories were also associated with increased risk for all components of ischemic events, including cardiac death (from 1.36% to 3.15%), MI (from 3.31% to 9.84%), stroke (3.31% to 6.10%) and definite/probable ST (from 0.58% to 1.97%), and all-cause mortality (from 2.14% to 6.30%) (All P trend<0.05). The net reclassification index after combined with 4 risk scores was 12.5% (5.3%-20.0%), 9.4% (2.0%-16.8%), 12.1% (4.5-19.7%), 10.7% (3.3-18.1%), which offered statistically significant improvement in the performance, compared with SYNTAX, residual SYNTAX, ACEF, and GRACE score, respectively. Conclusion: The novel multiple risk score model was significantly associated with the risk of long-term ischemic events in these patients with increment of scores. A meaningful improvement to predict adverse outcomes when multiple risk scores were applied to risk stratification.